Leaching experimental study on heavy metals in soil lead-zinc mine - Zhang Siyu; He Xuwen; Li Yan; Fang Zengqiang; Wang Hao (矿业科学学报, 2018)
To reveal the environmental behavior of heavy metals in lead-zinc mine soils under leaching conditions, the cumulative release characteristics of heavy metals in the soil under the leaching condition were determined by the leaching experiments.Furthermore, the first-order kinetic equation, the modified Elovich equation, the double-constant rate equation and the parabolic equation were applied to establish the release dynamic model of heavy metals in the soil.The results indicated that the leaching concentrations of heavy metals increased at first and then decreased slowly.The leaching concentrations had a certain negative correlation between leaching volume and pH, also had a certain positive correlation with electrical conductivity.The residual ratios of heavy metals in soil increased significantly, while the fraction proportions of extractable acetic acid decreased.Thereafter, the cumulative release rate of heavy metals gradually slowed down.Apart from the first-order kinetic equation, the fitting results of the other three equations was in a good agreement with the leaching process of heavy metals in the soil by the kinetic equation fitting.It indicates heavy metals' release processes of heavy metals in soil under simulated leaching conditions are not a simple first-order reaction, but a process of multifactor integrated control.